Determination of Mobility and Charge Carriers Concentration from Ionic Conductivity in Sodium Germanate Glasses above and below Tg. (11th February 2013) - Ferreira Nascimento, Marcio Luis
Abstract : The ionic conductivity and viscous flow data of x Na 2 O · ( 1 − x ) GeO 2, 0.05 < x < 0.296, have been collected in a large temperature range, below and above their glass transition temperatures (T g ). A microscopic model is proposed, assuming that the ionic displacement would result from the migration of interstitial positively charged cationic pairs whose concentration is an activated function of temperature. Below T g, their migration is also an activated mechanism, but a "free volume" would prevail above this temperature. This discontinuity in the migration mechanism justifies a Dienes-Macedo-Litovitz (DML) relationship to be representative of conductivity data above T g and an Arrhenius law below. According to this model, the enthalpy deduced by the fit of high temperature data using a DML equation would correspond to the charge carrier formation, whose migration enthalpy, below T g, could be deduced by the difference between the activation energy measured in the Arrhenius domain and the charge carrier formation enthalpy. To reduce the number of adjustable parameters numerical values were physically justified. We also applied a complete test for conductivity below T g, using the so-called weak electrolyte model, splitting activation enthalpy E σ A into formation and migration enthalpies and also explaining the variation of pre-exponential term of conductivity with composition.